Trends of and Factors Associated with Maternal Near-Miss in Selected Hospitals in North Shewa Zone, Central Ethiopia - Tesfay Brhane Gebremariam; Takele Gezahegn Demie; Behailu Tariku Derseh; Kalayu Brhane Mruts (Journal of Pregnancy)
Maternal near-miss (MNM) refers to a woman who nearly died but survived a complication that occurred during pregnancy, childbirth, or within 42 days of termination of pregnancy. Studies in Ethiopia showed an inconsistent proportion of MNM across time and in different setups. This study is aimed at assessing the magnitude, trends, and correlates of MNM at three selected hospitals in North Shewa Zone, Central Ethiopia. A hospital-based cross-sectional study was conducted among 905 mothers who gave birth from 2012 to 2017 in three hospitals using the WHO criteria for MNM. Medical records of the study subjects were selected using a systematic sampling technique. Data were retrieved using a pretested data extraction tool. Association between MNM and independent variables was assessed by using a binary logistic regression model. An odds ratio with a 95% confidence interval (CI) and p value of <0.05 were used to declare the level of significance. Of the 905 medical records reviewed, the prevalence of MNM was 14.3% (95%CI=11.9−16.6) and similar over the last six years (2012-2017). The magnitude of life-threatening pregnancy complications was found to be 12.7%; severe preeclampsia (31%) and postpartum hemorrhage (26%) account for the highest proportion. Admission at a higher level of obstetric care like referral hospital (AOR=4.85; 95% CI: 1.82-12.94) and general hospital (AOR=3.76; 95% CI: 1.37-10.33), not using partograph for labor monitoring (AOR=1.89; 95% CI: 1.17-3.04), history of abortion (AOR=2.52; 95% CI: 1.18-5.37), and any other pregnancy complications (AOR=6.91; 95% CI: 3.89-12.28) were factors significantly associated with higher MNM. Even though lower than the national figure, the proportion of MNM in the study area was very high, and there were no significant changes over the last six consecutive years. Giving special emphasis to women with prior history of pregnancy complications, hypertensive disorders of pregnancy, and obstetric hemorrhage with strict and quick management protocols and the use of partograph for labor monitoring are recommended to reduce the burden of severe maternal outcomes in the study area and Ethiopia.